Tanggung Jawab Perdata Notaris terhadap Akta yang Dibacakan oleh Staf Notaris di Hadapan Penghadap - Muhammad Tiantanik Citra Mido; I Nyoman Nurjaya; Rachmad Safa’at (University of Jember, 2018)
A notary in exercising powers to make an authentic deed is required to read it before an interlocutor as it is set in Article 16 paragraph (1) letter (m) Notary Act. The problem that arises is that, in some cases, notaries are not the only persons who exercise such duties. In fact, such role is often replaced by their staffs on duties entitled to them. It asserts that Notary Act is not extremely obeyed with following effects of the absence of laws in Notary Act which is specifically dealt with the role of notary’s staffs. This study uses empirical legal research with sociological jurisprudence approach. The result shows that a notary has attributive powers from Notary Act which is granted rights or powers to authorize staffs to act and exercize notary’s duties. To adhere with this view, a notary deed is seen as a perfect evidence if a notary did not accomplish certain procedures. However, if a notary cannot prove it, the declaration of a privately made deed should be made by judges of the courts. If there is any disadvantage as the result of deed read by staffs, a notary can be sued in the courts to provide compensation or certain terms as constituted in Article 1365 of the Civil Code, including maerial and immaterial compensations. Keywords: Civil Liability, Notary, Notary Staffs, Deed